Diatom-based indications of an environmental regime shift and droughts associated with seasonal monsoons during the Holocene in Biển Hồ maar lake, the Central Highlands, Vietnam - Hoàn, Đào-Trung; Fukumoto, Yu; Dương, Nguyễn-Thùy; Thành, Đinh-Xuân; Thái, Nguyễn-Đình; Unkel, Ingmar; Hướng, Nguyễn-Văn (The Holocene, 2024)
The interactions of the different monsoon systems across Southeast Asia create extreme climate phenomena. Central Vietnam, located near the centre of this transitional region, has encountered numerous effects. As a result, its sediments from lakes or speleothems are valuable archives for interpreting past climate variability. However, there is still a lack of high-resolution paleoenvironmental and palaeoclimatic reconstructions during the Holocene in Vietnam. Our study presents a paleoenvironmental diatom-based record of sediment cores collected from Biển Hồ maar lake (14°03′N, 108°00′E) in the Central Highlands of Vietnam covering nearly the entire Holocene. Based on changes in diatom assemblages in the sediment sequence, we identified two periods of the Early Holocene (~11,700-7800 cal BP) and the Mid- to Late-Holocene (~7800-360 cal BP), which mark a remarkable shift in the environment around Biển Hồ. Alternations of key diatom species during the Early Holocene indicate intensity variations between water-mixing and thermal stratification mechanisms in meso-eutrophic conditions. During the Mid- to Late-Holocene, the complete dominance of Aulacoseira granulata var. granulata implies year-round destratification and intense mixing of the lake water column in a permanently eutrophic environment. Its morphological variability reveals intervals of dry environmental conditions driven by pronounced droughts across the Asian continent.